Peran Akuntan Dalam Era Digital: Transformasi Profesi Dan Keterampilan Baru Dalam Menghadapi Teknologi Dan Tuntutan Pasar - Ningrum, Wulan Wahyu; Oktavia, Sarah; Jayanti, Fitri (Studia Economica : Jurnal Ekonomi Islam, 2024)
This paper aims to explore the impact of digital technology on the accounting profession and analyse the new skills required to meet the challenges. In the rapidly evolving digital era, the role of accountants has undergone significant transformation along with the penetration of technology in business practices. Through an in-depth literature review, this research reveals how automation, big data analytics and artificial intelligence have changed the accounting landscape. In addition, this research also highlights the importance of new skills such as data analysis, communication, risk management in navigating this digital era. The result in this study is that the role of accountants in the digital era has undergone a significant transformation. In the future, the accounting profession will be increasingly linked to technological developments. Although technology can automate administrative tasks, the role of accountants will become more focused on strategic analysis and business consulting. Although technology can replace tools, the role of humans in professional judgement remains irreplaceable due to the complexity of professional judgement required